Development of clinical trials for non-small cell lung cancer drugs in China from 2005 to 2023 - Jia, Wanying; Yu, Haiyan; Song, Li; Wang, Jian; Niu, Shuyu; Zang, Guojie; Liang, Mingjie; Liu, Jinwei; Na, Risu (Frontiers in Medicine, 2023)
Objective Over the past few decades, the development of anti-cancer drugs in China has made outstanding achievements based on the support of national policies. To assess the progress of non-small cell lung cancer (NSCLC) drugs, we conducted a statistical analysis of clinical trials of drugs targeting NSCLC in China from 2005 to 2023. Methods We downloaded, screened and analysed the data from three official websites, the Centre for Drug Evaluation of China National Medical Products Administration website (NMPA), ClinicalTrials.gov and the Chinese Clinical Trial Registry (ChiCTR). Results From January 1, 2005 to April 15, 2023, a total of 1,357 drug clinical trials that met the standards were included, and the number of registered drug clinical trials has been increasing year by year, reaching the maximum of 199 in 2021. Among them, the maximum of 462 items (34.05%) in phase II clinical trials, followed by 333 (24.54%) in phase III clinical trials, and 139 (10.24%) in phase IV clinical trials. In all drug clinical trials, industry sponsored trials (ISTs) have 722 items (53.21%), which are higher than investigator-initiated trials (IITs). The clinical trials of chemical drugs have a maximum of 723 items (53.28%), while biopharmaceuticals have grown rapidly in the past 10 years, with a total of 374 (27.56%), and 48.19% of the drug clinical trials of combined medication. In addition, the geographical distribution of the leading units and participating units of Chinese drug clinical trials are uneven, and economic regions such as Beijing, Shanghai, Jiangsu are obviously ahead of other regions. Conclusion From 2005 to 2023, the clinical trials of registered drugs for the treatment of NSCLC increased rapidly. Among them, due to the development of immunotherapy, the clinical trials of biopharmaceuticals and drugs for combined medication are growing most rapidly, while the exploration of the original drugs is a little far from enough. Our research provides a direction for the future drug clinical trials of NSCLC, laying foundation for further extending the survival rate of patients with NSCLC.